2015
DOI: 10.1016/j.carres.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical synthesis of nanostructured gold film for the study of carbohydrate–lectin interactions using localized surface plasmon resonance spectroscopy

Abstract: Localized surface plasmon resonance (LSPR) spectroscopy is a label-free chemical and biological molecular sensing technique whose sensitivity depends upon development of nanostructured transducers. Herein, we report an electrodeposition method for fabricating nanostructured gold films (NGFs) that can be used as transducers in LSPR spectroscopy. The NGF was prepared by electrodepositing gold from potassium dicyanoaurate solution onto a flat gold surface using two sequential controlled potential steps. Imaging b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…The significance of gold nanoparticles, gold films, gold nanostructure and nanoporous gold in various applications such as affinity biosensors, biocatalysis, and affinity separations is due to their frequently reported use as substrates for self-assembled monolayer (SAMs) formation [4750]. SAM formation is a method of functionalization of the substrate wherein the surface is modified in order to present functional groups, which are supported by well-defined and organized organic assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…The significance of gold nanoparticles, gold films, gold nanostructure and nanoporous gold in various applications such as affinity biosensors, biocatalysis, and affinity separations is due to their frequently reported use as substrates for self-assembled monolayer (SAMs) formation [4750]. SAM formation is a method of functionalization of the substrate wherein the surface is modified in order to present functional groups, which are supported by well-defined and organized organic assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…The flat gold surface was prepared by template stripping of sputtered gold from a silicon wafer. The details of this method were previously reported by our group [20]. The water contact angle was determined using a simple home-made setup (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The surface curvature may affect the orientation of alkanethiols and especially the spacing between the terminal functional groups, such as noted in a study showing that the p K a of carboxylic acid-terminated SAMs increases with nanoparticle diameter [16, 17]. The use of SAMs with specific terminal functional groups is important, such as when these groups are activated and coupled to biomolecules for use in development of biosensors [18–20]. In a previous study using thermogravimetric analysis (TGA), we found that the coverage of an alkanethiol SAM within an np-Au monolith was close to that expected on the basis of packing geometry on flat Au [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…and diluted further to the desired concentrations The SAM-modified gold wires were incubated in the desired concentration of lectins solution for 1 h at room temperature and thoroughly rinsed with Tris buffer and water before making the measurement. Our prior studies of Con A binding to SAMs containing Man-C 8 -SH [18] and of binding of the lectin soybean agglutinin to SAMs of a globotriose derivative[14] indicate that one hour is sufficient for binding equilibrium to be reached. Lectin PNA, which binds to galactosyl (β-1,3) N -acetylgalactosamine structures, was used as a negative control in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The K a value for methyl α-D-mannopyranoside reported in the study was 0.82 × 10 4 ( K d = 122 μM). More recently localized surface plasmon resonance [18], surface plasmon resonance (SPR) [19], quartz crystal microbalance (QCM) [20], and electrochemical techniques [21] have been used to investigate biomolecular interactions and have proven to play an important role in investigating carbohydrate–lectin interactions [22, 23]. …”
Section: Introductionmentioning
confidence: 99%